Pedagogical Approaches to the Formation of Cross-cultural Competence in Future Music Teachers (Journal of Educational Sciences, 2025)
The article examines the problems and prospects for developing cross-cultural competence in future music teachers. The research aims to determine the level of knowledge and the need for forming cross-cultural competence in the professional training of music students in higher education and to propose effective measures for its development. The main research directions included analyzing existing scientific concepts and approaches to forming cross-cultural competence in music education; determining the level of knowledge and significance of cross-cultural competence in the professional training model for music students at universities; developing and testing practical recommendations and methods for music teachers aimed at increasing the level of cross-cultural competence among students at music educational institutions. The research results expand theoretical knowledge about the significance of cross-cultural competence in training music educators, while the practical results present new methodological approaches.The empirical part of the study involved 98 students and 46 teachers from Abai Kazakh National Pedagogical University and Utemisov West Kazakhstan University. A survey of teachers and students showed that respondents believe the current state of cross-cultural competence requires significant improvements. Both groups identify similar problem areas and note some differences. Recognition of the need to develop cross-cultural competence among students was 48% and among teachers 40%, which demonstrates the relevance of this research. To form cross-cultural competence in future music teachers, a technology for developing this competence is proposed, including two special courses: "Teaching Intercultural Communication" and "Forming a High Level of Cross-Cultural Competence in Future Music Teachers." The pedagogical experiment showed that the experimental group demonstrates significantly greater progress across all levels of cross-cultural competence compared to the control group, with the lag being particularly noticeable at the creative level.Keywords: cross-cultural competence, pedagogical approaches, future music teachers, monocultural education, multicultural education, pedagogical model, development of cross-cultural competence.